High-fidelity delivery of kilowatt-level single-mode lasers through a tapered multimode fiber over one hundred meters - Xiao Chen; Shanmin Huang; Liangjin Huang; Zhiping Yan; Zhiyong Pan; Zongfu Jiang; Pu Zhou (High Power Laser Science and Engineering)
The immediate priorities for high-power delivery employing solid-core fibers are balancing the nonlinear effect and beam deterioration. Here, the scheme of tapered multimode fiber is experimentally realized. The tapered multimode fiber, featuring a 15 m (24/200 μm)–10 m (tapered region)–80 m (48/400 μm) profile, guides the laser with a weakly coupled condition. With the input power of 1035 W, the maximum output power over the 105 m delivery is 962 W, corresponding to a high efficiency of over 93% and a nonlinear suppression ratio of over 50 dB. Mode resolving results show high-order-mode contents of less than –30 dB in the whole delivery path, resulting in a high-fidelity delivery with M 2 factors of 1.20 and 1.23 for the input and output lasers, respectively. Furthermore, the ultimate limits of delivery lengths for solid-core weakly coupled fibers are discussed. This work provides a valuable reference to reconsider the future boom of high-power laser delivery based on solid-core fibers.